2002
DOI: 10.1046/j.1365-2435.2002.00658.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and food quality on anuran larval growth and metamorphosis

Abstract: Summary 1.Anurans exhibit high levels of growth-mediated phenotypic plasticity in age and size at metamorphosis. Although temperature and food quality exert a strong influence on larval growth, little is known about the interacting effects of these factors on age and size at metamorphosis. 2. Plasticity in growth rates, maximum larval mass, mass loss, larval period and size at metamorphosis was examined in Iberian Painted Frogs ( Discoglossus galganoi Capula, Nascetti, Lanza, Bullini & Crespo 1985) under diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
116
3
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(140 citation statements)
references
References 42 publications
(73 reference statements)
16
116
3
5
Order By: Relevance
“…Warming increased development rate more than growth rate in the absence of predators, while it increased growth rate more than development rate in the presence of predators, such that size at metamorphosis was reduced in the absence of predators but was increased in the presence of predators. The negative effect of warming on size at metamorphosis in the absence of predators is consistent with the prediction, based on the general rule for ectotherms, that increased temperature will facilitate development more than growth (Smith-Gill and Berven 1979), and it is also consistent with many experimental studies that show a reduced size at metamorphosis under higher temperatures (Newman 1998;Alvarez and Nicieza 2002;Tejedo et al 2010). However, the positive effect of warming on size at metamorphosis in Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Warming increased development rate more than growth rate in the absence of predators, while it increased growth rate more than development rate in the presence of predators, such that size at metamorphosis was reduced in the absence of predators but was increased in the presence of predators. The negative effect of warming on size at metamorphosis in the absence of predators is consistent with the prediction, based on the general rule for ectotherms, that increased temperature will facilitate development more than growth (Smith-Gill and Berven 1979), and it is also consistent with many experimental studies that show a reduced size at metamorphosis under higher temperatures (Newman 1998;Alvarez and Nicieza 2002;Tejedo et al 2010). However, the positive effect of warming on size at metamorphosis in Fig.…”
Section: Discussionsupporting
confidence: 89%
“…For instance, Newman (1998) found that Scaphiopus couchii metamorphosed earlier with a smaller size at metamorphosis at higher temperatures. This tendency has been further confirmed in many latter reports (Alvarez and Nicieza 2002;Laurila et al 2008; see also review by Tejedo et al 2010). However, such a tendency may not always hold true as there are often contrasting trait responses to specific environmental cues (Tejedo et al 2010).…”
Section: Introductionmentioning
confidence: 81%
“…Earlier work on amphibians (Browne and Edwards, 2003) has established that temperature influences food intake in frogs, and the effect of nutritional diets on growth rate and body mass of tadpoles (Alvarez and Nicieza, 2002). Briefly, the interaction of food quality and temperature noticeably altered larval size at metamorphosis: temperature changes of 5°C caused differences in growth rates in response to the same food diet.…”
Section: Discussionmentioning
confidence: 99%
“…Se utilizó el índice de antropización (IA) de Arribas et al (2002), adaptado por Nievas (2010), que incluye un total de 23 perturbaciones antrópicas a las que se les asignan valores, según la siguiente escala: 0 (nulo), 1 (bajo),clases de tamaño (LHC). Para estimar los efectos de temperatura del agua, caudal e índice de antropización sobre el crecimiento y desarrollo de las larvas se utilizó regresión lineal.…”
Section: Variables Ambientalesunclassified
“…Los anuros, además de presentar un ciclo de vida complejo, con estadios larvales que habitan cuerpos de agua y adultos principalmente terrestres, poseen características particulares, como la permeabilidad de los huevos y de la piel, que les facilita la absorción de distintos agentes ambientales. Estos, y otros aspectos biológicos y ecológicos, los ubican como indicadores potenciales de estrés ambiental (Barinaga, 1990;Blaustein y Wake, 1990;Wyman, 1990;Pechmann y Wilbur, 1994;Stebbins y Cohen, 1995). La pérdida de hábitat ocupa un lugar destacado en la lista de agentes que favorecen la disminución de especies de anfibios (Cushman, 2006), y la urbanización, en particular, ha sido citada como una amenaza clave para este grupo (Hamer y McDonnell, 2008).…”
Section: Introductionunclassified